Analisis Efektivitas Metode Ceramah dan Demonstrasi Terhadap Pengetahuan, Sikap dan Praktik Upaya Pencegahan Anemia Pada Remaja Putri - Angelia, Savira; Noor, Zairin; Herawati, Herawati; Sanyoto, Didik Dwi; Suhartono, Eko (Jurnal Ners, 2024)
The low level of efforts to prevent anemia in adolescent girls is one of the causes of the high rate of anemia in adolescent girls in the working area of ??the Bukit Hindu Community Health Center, Palangka Raya City, namely 49.82%. One effort to prevent anemia in young women is by promoting health through the video media Isi Piringku using lecture methods and demonstration methods which are expected to increase knowledge, attitudes and practices. To analyze the influence of the Isi Piringku video media using lecture and demonstration methods on the knowledge, attitudes and practices of young women. The research used a Quasi Experiment design with a pre-test and post-test group design approach. The total sample was 93 people, taken using a purposive sampling technique. The data obtained were then analyzed using the Wilcoxon statistical test for paired differences tests, and the Kruskall Wallis test for unpaired differences tests with a = 0.05. Based on the results of statistical analysis from research, it shows that all methods that have overall effectiveness have a p value <0.05. Of the 3 video media methods, Isi Piringku, which is more effective, uses lecture and demonstration methods in influencing changes in the level of knowledge, attitudes and practices of anemia prevention efforts among respondents. Using modified lecture and demonstration methods in conveying the contents of my plate video media about efforts to prevent anemia, the process of female students receiving the information presented will be more deeply impressive, thus forming a good and perfect understanding. The effectiveness of the contents of my plate video media with effective lecture and demonstration methods increases knowledge, attitudes and practices of preventing anemia